The Impacts of Cash Transfers on Women’s Empowerment : Learning from Pakistan’s BISP Program - Ambler, Kate; De Brauw, Alan (World Bank, Washington, DC, 2017)
Large-scale government cash transfer programs have become an important element of social protection and poverty reduction strategies throughout the developing world. Pakistan is no exception; in 2008, Pakistan established the Benazir Income Support Program (BISP) as an unconditional cash transfer targeted at the poorest of the poor. The primary goal of the BISP program is to provide the poorest households in Pakistan with unconditional transfers in order to improve their consumption and investments in children. To attain this goal, it is believed important that the transfers are provided directly to women to ensure the funds are spent as intended. Beyond changes in consumption and investment, directing these transfers to women can also serve to empower women by increasing household resources under their control. We analyze the impacts of Pakistan’s BISP program on women’s decision-making power within households using data collected between 2011 and 2013 as the program was rolling out. Using fuzzy regression discontinuity methods to statistically identify impacts, the BISP transfer is found to have substantial, positive impacts on some variables measuring women’s decision-making power and empowerment.